A snapshot of inorganic Janovsky complex analogues featuring a nucleophilic boron center. Issue 95 (2nd November 2017) - Wu, Di; Li, Yongxin; Ganguly, Rakesh; Kinjo, Rei
Abstract : The addition of phenyl lithium (PhLi) to an aromatic 1, 3, 2, 5-diazadiborinine (1) afforded isolable ionic species2, which can be deemed as an inorganic analogue of a Janovsky complex. Abstract : The addition of phenyl lithium (PhLi) to an aromatic 1, 3, 2, 5-diazadiborinine (1 ) afforded isolable ionic species2, which can be deemed as an inorganic analogue of a Janovsky complex. X-ray diffraction analysis and DFT studies of2 indicate the delocalization of π-type electrons mainly over the C–B–C unit in the central B2 C2 N2 six-membered ring. The reactions of2 with methyl iodide (MeI) and chloro(tricyclohexylphosphine)gold(i ) (Cy3 PAuCl) gave3 bearing a B–Me bond and4 featuring a B–Au bond, respectively, demonstrating the nucleophilic properties of the tricoordinate boron center in2 .